THE INFLUENCE OF ONLINE LEARNING ON STUDENTS' AWARENESS IN DOING ASSIGNMENTS DURING COVID-19 PANDEMIC - Maison Maison; Dw Agus Kurniawan; Lika Anggraini (Ta'dib, 2020)
Abstract: Learning that initially took place traditionally (face to face) has shifted to virtual learning or online learning. This study aimed to identify online learning's influence on students’ awareness of doing assignments during the Covid-19 pandemic. The mixed-method research with the sequential explanatory design was used to collect and analyze data with a total sample of 305 physics education students at Jambi University. The results showed that students' perceptions and awareness in carrying out tasks online are in a good category. There is a significant effect of online learning on student awareness in doing assignments with a contribution of 72.1%. The remaining 27.9% was influenced by other variables not found in this study. Abstrak: Pembelajaran yang semula berlangsung secara tradisional (tatap muka) telah bergeser ke pembelajaran virtual atau pembelajaran online. Penelitian ini bertujuan untuk mengetahui pengaruh pembelajaran online terhadap kesadaran mahasiswa dalam mengerjakan tugas selama pandemi Covid-19. Metode penelitian campuran dengan desain eksplanatori sekuensial digunakan untuk mengumpulkan dan menganalisis data dengan jumlah sampel sebanyak 305 mahasiswa Pendidikan Fisika Universitas Jambi. Hasil penelitian menunjukkan bahwa persepsi dan kesadaran mahasiswa dalam melaksanakan tugas secara online berada pada kategori baik. Ada pengaruh yang signifikan pembelajaran online terhadap kesadaran mahasiswa dalam mengerjakan tugas dengan kontribusi sebesar 72,1%. Sisanya 27,9% dipengaruhi oleh variabel lain yang tidak ditemukan dalam penelitian ini.